Paradigma Filosofis dalam Penanganan Korban Tindak Pidana Perdagangan Orang - Aisyah, Nurul Mutiara (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article aims to examine how philosophical perspectives or paradigms define the status and meaning of “victims” in human trafficking crimes, and how these paradigms shape ideal protection models beyond purely instrumental and repressive positive law approaches. This study applies a normative legal research method with a conceptual and philosophical approach. The daya is analyzed qualitatively through a process of interpretation and critical evaluation to explore the meaning, values, and paradigms contained in the legal text. It can be concluded that positive law in Indonesia, through the PTPPO Law, has defined victims in a progressive manner, not only as objects of crime but also as legal subject who have rights to be protected and restored. However, ontologically, in the formal process (KUHAP), the position of victims is still often marginalized by the criminal justice mechanism, which prioritizes the perpetrator (offender-oriented). A philosophical analysis of substantive legal constructs reflects high axiological values, namely restorative justice and the protection of human dignity. However, formal legal construct have not fully adopted epistemological values that are empathetic to the trauma of victims, thereby creatin the risk of re-victimization. The paradigm underlying this regulation is in tension between the retributive paradigm (imposition of sanctions) and the restorative paradigm (protection and recovery of victims). Therefore, it is recommended that the implementing regulations be clarified to be in line with the philosophical values contained in the PTPPO Law, and that in-depth socialization and training be provided to law enforcement officials regarding the paradigm of victims as subjects who are entitled to a trauma-informed justice process.